Ben-Hur - Wyler, William (Metro-Goldwyn-Mayer, 1995)
"A lavish,colorful spectacle that will linger long in the eye of the beholder" (New York Daily News), this cinematic master work tells the story of Ben-hur ( brilliantly portrayed by Charlton Heston), a Judean prince whose unjust arrest and unslavement culminates in a breathtaking chariot race, wherein he wreaks a shattering vengeance upon the Roman Tribune who destroyed his family. Winner of a record eleven Academy Awards-including Best Picture and Best Actor (Heston)- Ben Hur "ranks in the forefront of the great motion pictures of the screen's history" (Motion Picture Herald).